Enhancing sweet cherry resilience to spring frost and rain-induced cracking with pre-harvest melatonin treatments - M.C. Ruiz-Aracil; J.M. Valverde; A. Beltrà; J.M. Lorente-Mento; A. Carrión-Antolí; D. Valero; F. Guillén (Current Plant Biology)
Sweet cherry producers annually confront climatic challenges such as spring frost and fruit cracking. This vulnerability arises primarily from spring frost during bloom or cracking at critical maturity stages during persistent rainfall. With changing climate patterns, innovative strategies are essential to mitigate these adversities. Foliar applications of melatonin (MT) at 0, 0.01, 0.05 and 0.1 mM were tested on the ‘Prime Giant’ and ‘Sweetheart’ cultivars over four different production cycles (2020–2023) to evaluate the effect on frost resilience on flower buds and fruit cracking reduction. MT-treated flower buds showed reduced malondialdehyde content and increased fruit set in most seasons, reducing their vulnerability to extreme weather events. In addition, MT consistently decreased sweet cherry cracking incidence across all studied seasons, indicating a strong effect between the fruit ripening stage and susceptibility to fruit cracking, which was cultivar dependent. Quality parameters at harvest, including fruit firmness, and colour at harvest, were either delayed or unaffected in MT-treated fruits compared with controls. However, other ripening parameters were stimulated by pre-harvest MT applications in several growing cycles, such as total soluble solids, which slightly reduced total acidity in MT-treated fruits. In summary, pre-harvest MT treatments can be a promising strategy for climate change adaptation and stress mitigation, potentially increasing sweet cherry production under extreme weather conditions.